Superoptimal Rate of Convergence in Nonparametric Estimation for Functional Valued Processes. (16th September 2014) - Chesneau, Christophe; Maillot, Bertrand
Abstract : We consider the nonparametric estimation of the generalised regression function for continuous time processes with irregular paths when the regressor takes values in a semimetric space. We establish the mean-square convergence of our estimator with the same superoptimal rate as when the regressor is real valued.